Fruit/Seed Setting in Teak (Tectona grandis L.F) : a Point to Ponder - Rawat, M. S. (Indian Forester, 1994)
Teak is the most important timber species of the Indian sub-continent and one of the most important of the world. With the ever increasing demand of more and more wood of superior quality it has become the need of paramount nature to produce superior seed for better and always increasing plantation targets. As seed production is much below the expectations the reasons for the same have been given along with some very interesting observations.